2020
DOI: 10.1001/jamanetworkopen.2020.17348
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Standardized Patients vs Academic Training for Learning Motivational Interviewing Skills in the US Department of Veterans Affairs and the US Military

Abstract: IMPORTANCE Despite the need for effective and scalable training in motivational interviewing (MI) that includes posttraining coaching and feedback, limited evidence exists regarding the effectiveness of using virtual (computerized) standardized patients (VSPs) in such training. OBJECTIVE To evaluate the efficacy of training with a VSP on the acquisition and maintenance of MI skills compared with traditional academic study. DESIGN, SETTING, AND PARTICIPANTS This study was a 2-group, parallel-training randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…A 2020 study of 122 practicing Veteran’s Administration providers examined the effect of a computer simulation to train motivational interviewing skills (i.e., Motivational Interviewing Novice Demonstration ) in comparison to a self-study control. The study found effects on three Motivational Interviewing Treatment Integrity indicators (i.e., technical and relational scores, question to reflection ratio) that were maintained up to a 3-month follow-up (Reger et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A 2020 study of 122 practicing Veteran’s Administration providers examined the effect of a computer simulation to train motivational interviewing skills (i.e., Motivational Interviewing Novice Demonstration ) in comparison to a self-study control. The study found effects on three Motivational Interviewing Treatment Integrity indicators (i.e., technical and relational scores, question to reflection ratio) that were maintained up to a 3-month follow-up (Reger et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the studies above made motivations the focus of their research, an additional 31 studies 41–72 indirectly addressed physicians' motivations to engage or not in simulation-based CPD. Findings were limited mainly to descriptions of the nature of incentives used by study authors to recruit physicians in studies involving simulation-based CPD, such as insurance premium discounts, 44 CME credits, 45 institutional or departmental requirements, 39 financial incentives, 62 financial compensation for missed paid work, 71 work scheduling accommodations, 58 or a combination of incentives 59 were reported.…”
Section: Resultsmentioning
confidence: 99%
“…The novel virtual clinical experiences involved synchronous interactions with standardized clients without formal assessment, providing students with low stakes, hands on clinical experience in a safe environment. While randomized controlled trials have been conducted comparing traditional learning with virtual patients (Reger et al., 2020; Stevens et al., 2006), these virtual experiences have tended to focus on asynchronous, computerized simulation (Kleinheksel, 2017). The use of virtual clinical placement experience appears to be a novel concept in the education of health professional students.…”
Section: Discussionmentioning
confidence: 99%